ANALISIS RASCH MODEL: VALIDITAS DAN RELIABILITAS INSTRUMEN KORBAN BULLYING - Putri, Mia Aprianti; Suryana, Dodi; Supriatna, Mamat; Yudha, Eka Sakti (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
The phenomenon of bullying is still rife among high school adolescents in Indonesia. This study aims to develop an instrument that measures the number of victims of bullying at school. The study involved adolescents with an age range of 12-14 years at a junior high school in West Bandung Regency, West Java, Indonesi a. This study used a quantitative method with a questionnaire containing 18 items which had 4 Likert answer choices. Data analysis used the Rasch model approach, and used Winstep 3.73 software. The results of the analysis show that personal reliability is 0.49 which indicates that the consistency of participants in answering questions is included in the weak category, and item reliability is 0.95 which indicates that the quality of the item items is classified as special. It can be concluded that the instrument for victims of bullying already has items that are classified as special, it's just that the consistency of participants in answering questions is still weak, and the level of interaction between participants and items is also lacking. Keywords: Validity, reliability, Rasch model, victims of bullying